Pengaruh Kepercayaan dan Kenyamanan Terhadap Loyalitas dengan Kepuasan Pasien Rawat Jalan Sebagai Intervening di Klinik Mata Tritya Surabaya - Kurniawan, Mateus Andhi; Wibowo, Bima Ardiyanto; Mujanah, Siti; Fianto, Achmad Yanu Alif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Customer satisfaction is one of the things that triggers customer loyalty to a product or service. This study investigates the effect of trust and convenience on customer satisfaction. It also investigates whether customer satisfaction is a good mediator. This study surveyed patients at Tritya Eye Clinic Surabaya. Using purposive sampling method with sample criteria being patients who have been treated at the Clinic, 152 respondents were obtained. The data was then analyzed using Structural Equation Modeling. The findings show that trust and convenience contribute positively to customer satisfaction. The study also proved that customer satisfaction mediates the relationship of trust and convenience to customer loyalty. This study contributes to understanding marketing management using the trust and convenience framework in healthcare companies, which can also be applied to other general companies.